Relationship Of The Mother’s Role In The Development Of Preschool Children In The Holsa Administrative Post Maliana Maliana Municipaly, Bobonaro Timor-Leste 2022 - Ximenes da Conceição, José; Jose Tilman, Etelvina; Carvalho de Araújo, Eugenia; Ximenes, António; Guterres Pereira, Acácio; Antonia dos Santos, Anagilda (CV RIFAINSTITUT, 2023)
The development of preschool children is very important because children will be able to adapt to the environment with physical development and psychosocial development, Sigmud Freud (2019) to know the relationship of the mother's role in the development of preschool children in the holsa, Administrative post Maliana, Bobonaro, Timor-Leste 2022. Research methods: The researcher used the quantitative descriptive method with a cross-sectional approach. The research sampling technique used non-probabilistic and intentional sampling. The instrument used by the researcher was a questionnaire and observation of the DDST. Researcher ensures that the information used is an additional skill for mothers and preschool children aged 4 to 6 years. the research shows that there is a relationship between the role of the mother and child development, using SPSS version 24.0. The analysis of the cross-spearmen ranks test showed that the P value was 0.001 < 0.05, with the spearmen's correlation 0.619, the strength of the correlation index. The role of mothers in kindergarten is almost half that of the moderate mother. The development of preschool children in kindergarten is almost entirely normal and there is a relationship between the role of the mother and the development of preschoolers in early childhood education.